Między przestrzenią Mediolanu a pamięcią poetycką. Rozważania na marginesie włoskiej poezji współczesnej - Polanowska, Patrycja (Zagadnienia Rodzajów Literackich, 2023)
In contemporary Italian poetry, the strong presence of things intertwines with the recognition of emptiness. Poets, freed from the excess of history, rebuild their relationship with reality. They discover the depth of things and their real duration. At the same time, they try to find their own identity. A strong interdependence between the subject and the space takes a particular form in the works of poets associated with Milan, such as Vittorio Sereni or Milo De Angelis. They construct poetic imagery through liminal spaces and overlapping visions. Their poetic chronotope does not belong to the linear development of history. Starting from these observations, we aim to understand Milan’s character revealed by contemporary poetry. The dominance of non-places, indicated by Marc Augé, is contrasted in the paper with traditional spatial practices, such as wandering around the streets, where, as in Barthes: “the city speaks to its inhabitants, we speak our city, simply by inhabiting it, by traversing it, by looking at it.” This approach finally leads us to see the poetic space from the microhistory perspective and through the aura phenomenon.